Effect of Heating on Tensile Strength and Elongation at Break of Bioplastic from Taro Starch Filled Chitosan (Colocasia esculenta) with Glycerol Plasticizer - Ginting, M.H.S.; Hasibuan, R.; Lubis, M.; Sirait, T.P.; Sidabudar, T. (Asian Journal of Chemistry, 2021)
Taro starch is a potential raw material for bioplastics by adding glycerol and chitosan. The casting method is used for making bioplastics with 30%w/v starch solution. Moreover, the variation added volume of glycerol (1%, 2% and 3% v/v), addition of chitosan (1% w/v, 2%w/v and 3%w/v) and pasting temperature was 75 ºC. Taro starch with particle size 100 mesh has 93.55% starch, 17.9% amylose, 75.66% amylopectin. Analysis of plastice properties showed that taro starch has a gelatinization temperature of 74.52 ºC with high peak viscosity 5953.5 cP. FTIR analysis show bands due to presence of O-H, C-H, C=H, C-O-H and C-O. The best of bioplastic in this study was 30% w/v on starch, 1% v/v glycerol and 2% w/v chitosan at 75 ºC produces 42.86% water absorption, 8.297 MPa tensile strength and elongation at break was 45.846%.